2013
DOI: 10.1371/journal.pone.0081250
|View full text |Cite|
|
Sign up to set email alerts
|

Caco-2 Cell Acquisition of Dietary Iron(III) Invokes a Nanoparticulate Endocytic Pathway

Abstract: Dietary non-heme iron contains ferrous [Fe(II)] and ferric [Fe(III)] iron fractions and the latter should hydrolyze, forming Fe(III) oxo-hydroxide particles, on passing from the acidic stomach to less acidic duodenum. Using conditions to mimic the in vivo hydrolytic environment we confirmed the formation of nanodisperse fine ferrihydrite-like particles. Synthetic analogues of these (~ 10 nm hydrodynamic diameter) were readily adherent to the cell membrane of differentiated Caco-2 cells and internalization was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 74 publications
4
70
0
1
Order By: Relevance
“…One of the most innovative preparation is "sucrosomial" iron (SI), that is a source of ferric pyrophosphate covered by phospholipids plus sucrose esters of fatty acids matrix [84]. In vitro experiments on human intestinal Caco-2 cells suggest that SI could be taken up through a DMT-1 independent mechanism [84], possibly through endocytosis and similarly to what happens with nanoparticles [85,86] (see below). Whether this occurs also in vivo, as well as whether SI utilizes unique mechanisms also to enter the bloodstream remain to be proven.…”
Section: New Preparationsmentioning
confidence: 99%
“…One of the most innovative preparation is "sucrosomial" iron (SI), that is a source of ferric pyrophosphate covered by phospholipids plus sucrose esters of fatty acids matrix [84]. In vitro experiments on human intestinal Caco-2 cells suggest that SI could be taken up through a DMT-1 independent mechanism [84], possibly through endocytosis and similarly to what happens with nanoparticles [85,86] (see below). Whether this occurs also in vivo, as well as whether SI utilizes unique mechanisms also to enter the bloodstream remain to be proven.…”
Section: New Preparationsmentioning
confidence: 99%
“…Powell showed data from recent studies demonstrating that nano-Fe 3þ crosses the apical surface of Caco-2 cells via an endocytic pathway before being dissolved in endosomes or lysosomes inside the cell (figure 5), and that its subsequent homeostasis is under the normal regulatory control of dietary iron absorption, namely via ferroportin-dependent efflux from enterocytes. This suggests that nano-Fe 3þ thus offers potential as a novel oral iron supplement with enhanced uptake in the nano form followed by release and processing in the body via the normal soluble iron pathway [25]. Also approaching the topic from a clinical perspective, Andre Nel (University of California, Los Angeles) discussed existing data that supports predictive modelling and alternative testing strategies for regulatory decision making regarding nanomaterials.…”
Section: (D) Interactions Of Nanomaterials With the Human Body: Nanosmentioning
confidence: 99%
“…For example, Jahn et al (2011) studied the uptake of hemin-coupled iron hydroxide NPs on Caco-2 cells and they speculated a strong effect due to the colloidal stability of such NPs in the medium, but they did not perform any stability study. Pereira et al (2013) found that Fe(III)-oxo hydroxide NPs forms ferrihydrite-like complexes after a simulated in vitro digestion. PC NPs could not be isolated from GI fluids without aggregation, but they used the approach to synthesize ferrihydrite complexes ex novo for studying their biological response on Caco-2 cells, bypassing the isolation of such NPs from digestive fluids.…”
Section: Stability Of Nps In Simulated Gastrointestinal Fluidsmentioning
confidence: 96%